Herbicide resistant weeds as place disruption: Their impact on farmers' attachment, interpretations, and weed management strategies. (December 2018) - Dentzman, Katherine
Highlights: Using SEM and EFA, the following patterns emerge for U.S. corn and soybean farmers. Herbicide resistant weeds increase farmers' farm and community place attachment. Farmers' place attachment leads to different interpretations of herbicide resistance. Farmers' interpretations of herbicide resistance impact weed management behaviors. Place attachment and community involvement are important factors in weed management.